Alternative fining of Sangiovese wine: effect on phenolic substances and sensory characteristics. (6th December 2020) - Rinaldi, A.; Errichiello, F.; Moio, L.
Abstract: Background and Aims: In recent years, alternative fining practices have increasingly been adopted by the wine industry. The use of plant proteins, as alternatives to traditional fining agents of animal origin for clarification, meets the expectations of a safe product. The effect of alternative fining practices was studied in Sangiovese wine. Methods and Results: Four wines of variable phenolic composition were fined with a protein of vegetable origin (patatin) and one of animal origin (gelatin) at 5 and10 g/hL, and the influence on phenolic substances (colour parameters, CIElab coordinates, polymeric pigments, anthocyanins, flavans reactive to vanillin, tannins reactive to bovine serum albumin and saliva) and sensory characteristics (astringency, bitterness, astringency subqualities, odour, and aroma) compared. Colour showed that the efficiency of fining depends on: dose for high tannin wine and protein type for wines with a low concentration of anthocyanins. Astringency decreased in high tannin wine and bitterness in low anthocyanin wine following fining. Fined wines resulted in improved astringency subqualities and aroma descriptors. Conclusions: The efficacy of traditional and alternative fining practices is influenced by the composition of wine phenolic substances. Significance of the Study: Due to the potential allergenicity of animal proteins, plant proteins represent a safe and healthy alternative to the traditional fining of Sangiovese wine.